2014
DOI: 10.2527/jas.2013-7019
|View full text |Cite
|
Sign up to set email alerts
|

Residual feed intake studies in Angus-sired cattle reveal a potential role for hypothalamic gene expression in regulating feed efficiency1,2

Abstract: Mechanisms underlying variation in residual feed intake (RFI), a heritable feed efficiency measure, are poorly understood while the relationship between RFI and meat quality is uncertain. To address these issues, 2 divergent cohorts consisting of High (HRFI) and Low (LRFI) RFI individuals were created by assessing RFI in 48 Angus-sired steers during a 70 d feeding trial to identify steers with divergent RFI. The association of RFI with indices of meat quality and expression of genes within hypothalamic and adi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 68 publications
4
33
2
2
Order By: Relevance
“…Perkins et al (2014) reported significant differences in the mRNA expression of leptin and NPY between high and low RFI Angus-sired cattle. They attributed these differences to hypothalamic neuropeptide gene expression, concluding that these might underlie variation in feed efficiency and that the gonadotropin axis might also influence the RFI [8]. In common with their study, we found that LEP, JAK1, LEPR, STAT, and SOCS3 were down-regulated and that NPY was up-regulated in the low RFI group based on the gene-chip microarrays (Fig.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Perkins et al (2014) reported significant differences in the mRNA expression of leptin and NPY between high and low RFI Angus-sired cattle. They attributed these differences to hypothalamic neuropeptide gene expression, concluding that these might underlie variation in feed efficiency and that the gonadotropin axis might also influence the RFI [8]. In common with their study, we found that LEP, JAK1, LEPR, STAT, and SOCS3 were down-regulated and that NPY was up-regulated in the low RFI group based on the gene-chip microarrays (Fig.…”
Section: Discussionsupporting
confidence: 59%
“…Perkins et al (2014) found that neuropeptide-Y (NPY), relaxin-3 (RLN3), the melanocortin 4 receptor (MC4R), and gonadotropin-releasing hormone (GnRH) mRNA expression were 64%, 59%, 58%, and 86% lower, respectively, in the arcuate nucleus of low RFI steers, whereas gonadotropin inhibiting hormone (GnIH) and pro-opiomelanocortin (POMC) mRNA expression was 198% and 350% higher than the high ones. Serum tests among different RFI coefficients have been greatly researched because of the easily obtained samples in dairy cattle [8]. Kelly et al (2010) measured concentrations of insulin-like growth factor-1 (IGF-1), insulin, and various metabolites in finishing heifers, and found that insulin concentrations were correlated with RFI [9].…”
Section: Introductionmentioning
confidence: 99%
“…Further, the biological basis for high efficiency in Group Low RFI is thought to be due to better energy and protein metabolism (Karisa et al 2014), improved mitochondrial respiration rate (Kolath et al 2006), increased gene expression of gut microorganisms (Bezerra et al 2013) or hypothalamus (Perkins et al 2014) as observed for Angus-sired cattle. Altogether these factors could improve feed efficiency.…”
Section: Composition Of Diets Residual Feed Intake Performance and mentioning
confidence: 94%
“…RFI is the difference between actual intake and the expected requirements of feed for maintenance and body weight gain and is independent of mature weight and average daily gain (ADG) (Nkrumah et al 2006;Lawrence et al 2013;Steyn et al 2014) and thus will be desirable as a nutritional tool for genetic improvement of the livestock (reviewed by Bezerra et al 2013). RFI, being moderately heritable (h 2 for cattle ranges from 0.25 to 0.49), has been studied as a selection method for feed efficiency in beef cattle (Kolath et al 2006;Nkrumah et al 2006;Hegarty et al 2007;Jones et al 2011;Perkins et al 2014), dairy cows (Lawrence et al 2013;Steyn et al 2014), Murrah buffaloes (Bisitha et al 2014), sheep (Muro-Reyes et al 2011Redden et al 2014), pigs (Grubbs et al 2013), chicken (Zhen-qiang et al 2014), rabbits (Larzul and de Rochambeau 2005) and minks (Hedemann and Damgaard 2012), although mechanisms underlying variation in RFI are poorly understood (Perkins et al 2014). Recently, Berry and Crowley (2013) and Bisitha et al (2014) concluded that RFI is an effective and robust index of feed efficiency evaluation in growing bovines.…”
Section: Introductionmentioning
confidence: 99%
“…Since about two-thirds of the cost of producing beef is due to the expense of feed inputs, strategies that improve efficiency of feed utilization will substantially increase the economic viability of beef production systems. In fact, Weaber (apud Perkins et al, 2014) estimated that the U.S. beef industry could save $1 billion annually by reducing residual feed intake (RFI) by 10% (equivalent to reducing daily intake by 0.9 kg per animal). Furthermore, as improvements in feed efficiency will also reduce nutrient excretions and GHG emissions (Waghorn and Hegarty, 2011), discovery and adoption of technologies to enhance genetic merit for feed efficiency is arguably one of the most cost-effective strategies available to meet future demands for animal protein in a more sustainable manner.…”
Section: Selection Strategies For Efficient Meat Productionmentioning
confidence: 99%